ING UNIVERSITY BULLETIN English Русский Українська FONT SIZE Make font size smallerMake font size defaultMake font size larger JOURNAL CONTENT Search Search Scope All Browse By Issue By Author By Title By Sections Other Journals Categories CURRENT ISSU - Рудевська, Вікторія; Погоріла, Олена (Socio-economic relations in the digital society, 2020)
Given the priority of the European vector of integration processes in Ukraine, improving the system of state regulation of the market of non-banking financial services, in particular the insurance market, gainstrategic importance. Ensuring an effective mechanism for the operation of insurance companies is one of the important elements on the way to integration into a common harmonized financial market. The purpose of the article is to analyze trends and prospects for state regulation of the insurance market in Ukraine and developrecommendations for its optimization on the way to creating a transparent, solvent and competitive insurance market in the current realities of the financial sector of Ukraine. Authors conducted an analysis of the current state of the insurance market, identified a number of unresolved issues hindering its development. Also, the level of insurance penetration in Ukraine and European countries, the degree of concentration of the insurance market, the level of capitalization of insurance market of Ukraine (in dynamics) are analyzed. Trends in the development of the insurance market in Ukraine and abroad are studied. Obstacles to the development of the insurance market in Ukraine are presented. The main directions of reforming the insurance market of Ukraine in accordance with the vision of The National Bank of Ukraine of the insurance market’s of Ukraine future regulation are described. The author considers the foreign experience of the single financial mega regulator, as well as the features and possible effect of its implementation on the basis of the National Bank of Ukraine. A comparative analysis of the main differences between the Solvency I and Solvency II directives is done. The possibilities and expected consequences of the implementation of the requirements of the Solvency II Directive in the activities of Ukrainian insurance companies are assessed. The tasks facing the new regulator of the insurance market are given. Emphasis was placed on the importance of ensuring an acceptable process for insurance companies to exit the market, as well as the need to create a system of guaranteeing payments under long-term life insurance contracts (based on foreign experience — the use of the Ex-ante model).
Keywords: insurance; insurance market; «split»; government regulation; megaregulator; Solvency I; Solvency II